THE IMPACT OF COVID-19âS PANDEMIC ON THE ECONOMY OF WEST JAVA USING SPATIAL REGRESSION - Nathanael Wongso, Ryan
COVID-19 is a new type of disease that was first d iscovered i n Wuhan, China, in 2019. The virus from COVID-19 rapidly spread and infected many people throughout the globe, including in West Java, Indonesia. Therefore, it becomes a global pandemic in no time. The COVID-19 pandemic requires the government to implement Large-Scale Social Restrictions that shut down various West Java activities. This has dramatically affected the economy in West Java, as seen from the decline in the value of the Gross Regional Domestic Product (GRDP) in the second quarter of 2020. The effect of the COVID-19 pandemic on the economy of 27 cities or districts in West Java can be seen using the spatial regression method. The COVID-19 variables used are population, number of confirmed cases, number of people isolated, recovered and died. Meanwhile, the economic variable used is the difference in the value of GRDP in the first and second q uarters. The spatial regression models used are the Spatial Autoregressive Model (SAR), the Spatial Error Model (SEM), and the Spatial Autoregressive Moving Average (SARMA). Modelling is done by using four alternatives to produce and select the best model. Moran’s I test the spatial effect on the model. The Lagrange Multiplier tests the best spatial regression model. The error assumption tests the characteristics of errors in the model. The Wald tests significant variables. SARMA is the best spatial regression modelling produced that shows that more dead people will negatively impact the economy. Meanwhile, the more isolated and recovered people will positively impact the economy of West Java.